Pengaruh Kualitas Pelayanan Program Pascasarjana Universitas Muhammadiyah Metro Lampung terhadap Loyalitas Mahasiswa Kuliah di Program Pascasarjana Universitas Muhammadiyah Metro - Sari, Dwi Harum Puspa; Suharto, Suharto; Dacholfany, M. Ihsan (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the effect of the Postgraduate Program's service quality at Muhammadiyah University of Metro Lampung, which consists of tangible assurance, empathy, reliability, and responsiveness to the Postgraduate Program's student loyalty Muhammadiyah University of Metro Lampung. This research's research type is quantitative research, namely research by obtaining data in the form of numbers or estimated quantitative data. According to Sugiyono (2014: 38), this study aims to determine the effect of service quality at the Postgraduate Program, Muhammadiyah University Metro Lampung on student loyalty in the Postgraduate Program at Muhammadiyah University Metro Lampung.The result of this research is that the tangible variable ξ1 has a significant effect on the variable η1 reliability with the value of tcount= 0.516 at a = 0.05 where the ttable = 1.67 is obtained because the tcount> of the ttablevalue, the ξ2 assurance variable has a significant effect. Directly to the variable η1 reliability with a value of tcount= 0.111 at a = 0.05, it is obtained t table= 1.67, variable ξ3 emphaty does not have a direct influence on the variable η1 reliability with a value of tcount = 0.108 at a = 0.05 is obtained t table= 1.67, the ξ1 tangible variable has no influence on the η2 responsiviness variable, with the value of tcount= 0.936 at a = 0.05, obtained t table= 1.67, the ξ3 emphaty variable has a direct significant effect on the η2 responsiviness variable with the tcount= 0.021 at a = 0.05 is obtained ttable= 1.67, variable η2 responsiviness to variable η3 loyalty has a direct influence from the calculation of tcount= 0.00 at a = 0.05 is obtained t table= 1.67, variable ξ1 tangible to the direct significant effect on the loyalty variable η3 with a value of tcount= 0.30 at a = 0.05 obtained t table= 1, 67, variable ξ3 empahty to variable η3 loyalty from the value tcount = 0.02 at a = 0.05 is obtained t table= 1.67, variable η2 responsiviness has a direct significant effect on the loyalty variable η3 from the value tcount= 0.42 in a = 0.05, the obtained ttable= 1.67. Thus, these results indicate that the empathy variable has no effect on reliability in the Postgraduate Program, Muhammadiyah University of Metro Lampung. The tangible variable does not affect responsiveness in the Postgraduate Program, Muhammadiyah University of Metro Lampung.